PENGARUH pH TERHADAP AKTIVITAS PENISILIN G ASILASE OLEH ISOLAT BAKTERI DARI AIR BATANG ARU LUBUK BEGALUNG KOTA PADANG - Ningsih, Dini Yusta Prestu; Fifendy, Mades; Megahati Siregar, RRP (STKIP PGRI Sumbar, 2013)
Natural Penicillins (penicillin G) is known as an antibiotic which is chemically unstable, such as the onset of allergic in the body and its narrow spectrum. We perform the repairproperties of penicillin that makes penicillin G derivatives, in order to obtain a semisyntheticpenicillin that are better. Development of new penicillin can be reached by modifying thechemical spectrum penicillin G into 6-APA which is at the core of penicillin. To hydrolyzepenicillin G into 6-APA required the PGA enzyme produced by bacteria. PGA is anequilibrium reaction activity is influenced by pH. Under these conditions, has done research onthe effect of pH on PGA activity by bacterial isolates from Air batang Aru Lubuk BegalungPadang. The purpose of this study was to determine the effect of pH on PGA activity bybacterial isolates from Air Batang Aru. The research was conducted in the laboratory KopertisX from October 2012 to January 2013. This study is an experimental study with the method ofKornfeld on variation between pH (6.5, 7.0, 7.5, and 8.0). These results indicate that the pHeffect on the activity of PGA at pH 6.5 variation (0.0076 U / ml), pH 7.0, (0.0114 U / ml), pH7.5 (0.0609 U / ml ), and pH 8.0 (0.0200 U / ml). PGA optimum activity produced by bacteriaisolates were at pH 7.5